Immune Axonal Neuropathies Associated With Systemic Autoimmune Rheumatic Diseases - Tulbă, Delia; Popescu, Bogdan Ovidiu; Manole, Emilia; Băicuș, Cristian (Frontiers in Pharmacology, 2021)
Immune axonal neuropathies are a particular group of immune-mediated neuropathies that occasionally accompany systemic autoimmune rheumatic diseases such as connective tissue dissorders and primary systemic vasculitides. Apart from vasculitis of vasa nervorum, various other mechanisms are involved in their pathogenesis, with possible therapeutic implications. Immune axonal neuropathies have highly heterogeneous clinical presentation and course, ranging from mild chronic distal sensorimotor polyneuropathy to severe subacute mononeuritis multiplex with rapid progression and constitutional symptoms such as fever, malaise, weight loss and night sweats, underpinning a vasculitic process. Sensory neuronopathy (ganglionopathy), small fiber neuropathy (sensory and/or autonomic), axonal variants of Guillain-Barré syndrome and cranial neuropathies have also been reported. In contrast to demyelinating neuropathies, immune axonal neuropathies show absent or reduced nerve amplitudes with normal latencies and conduction velocities on nerve conduction studies. Diagnosis and initiation of treatment are often delayed, leading to accumulating disability. Considering the lack of validated diagnostic criteria and evidence-based treatment protocols for immune axonal neuropathies, this review offers a comprehensive perspective on etiopathogenesis, clinical and paraclinical findings as well as therapy guidance for assisting the clinician in approaching these patients. High quality clinical research is required in order to provide indications and follow up rules for treatment in immune axonal neuropathies related to systemic autoimmune rheumatic diseases.